2020
DOI: 10.21203/rs.3.rs-26929/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enhanced therapeutic effects of umbilical cord mesenchymal stem cells after prolonged treatment for HBV- related liver failure and liver cirrhosis

Abstract: Background: This study aimed to investigate the therapeutic effect of umbilical cord mesenchymal stem cells (UCMSCs) on HBV-related liver failure and liver cirrhosis and to compare the different efficacies of UCMSCs after different treatment courses.Methods: This was an observational study that retrospectively considered a three-year period during which 513 patients who received stem cell infusion met the criteria of hepatic failure and liver cirrhosis were identified from databases of the Third Affiliated Hos… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…The results of previous studies from our department showed that allogeneic bone marrow-derived MSCs are effective and safe for HBV-related ACLF patients (8,9). In our last study, we observed that umbilical cord mesenchymal stem cells (UCMSCs) also showed good therapeutic effects for HBV-related ACLF and liver cirrhosis, and this therapeutic effect could be enhanced by prolonging the UCMSC treatment course, especially for patients with cirrhosis (10). However, a series of factors in uencing the therapeutic effects of MSCs during the treatment of liver failure and cirrhosis have also been proposed by other scholars, such as the type of MSCs, the method of infusion, the dosage of infusion, and the time of infusion (11).…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…The results of previous studies from our department showed that allogeneic bone marrow-derived MSCs are effective and safe for HBV-related ACLF patients (8,9). In our last study, we observed that umbilical cord mesenchymal stem cells (UCMSCs) also showed good therapeutic effects for HBV-related ACLF and liver cirrhosis, and this therapeutic effect could be enhanced by prolonging the UCMSC treatment course, especially for patients with cirrhosis (10). However, a series of factors in uencing the therapeutic effects of MSCs during the treatment of liver failure and cirrhosis have also been proposed by other scholars, such as the type of MSCs, the method of infusion, the dosage of infusion, and the time of infusion (11).…”
Section: Introductionmentioning
confidence: 81%
“…A large-scale meta-analysis of randomized controlled trials (RCTs) evaluating the therapeutic effects and safety of stem cell therapy for chronic liver disease (CLD) revealed that stem cell therapy is a safe and effective therapeutic option for CLD and that patients with ACLF bene t the most in terms of improved short-term survival rates (20). The results of our previous research showed that UCMSCs also have good therapeutic effects for HBV-related ACLF and liver cirrhosis and that their therapeutic effect could be enhanced by prolonging the UCMSC treatment course (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We selected ACLF of type A in this study. The exclusion criteria of the patients were as previously described [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…The results of previous studies from our department showed that allogeneic bone marrow-derived MSCs are effective and safe for HBV-related ACLF patients [ 8 , 9 ]. In our last study, we observed that umbilical cord mesenchymal stem cells (UCMSCs) also showed good therapeutic effects for HBV-related ACLF and liver cirrhosis, and this therapeutic effect could be enhanced by prolonging the UCMSC treatment course, especially for patients with cirrhosis [ 10 ]. However, a series of factors influencing the therapeutic effects of MSCs during the treatment of liver failure and cirrhosis have also been proposed by other scholars, such as the type of MSCs, the method of infusion, the dosage of infusion, and the time of infusion [ 11 ].…”
Section: Introductionmentioning
confidence: 99%